Rose (Watkins) Katzenellenbogen and Family Pre-Move to California - Watkins, Howard::::::::: (1988)
Rose Katzenellenbogen, Taube Ager Weiner Katzenellenbogen, Irving Fine, Esther Weiner Fine, Leibe Solkolovsky, and Beatrice (Batsheva) Katzenellenbogen 1936 New York City Portrait format